PERFORMA MESIN BENSIN 113,7 CC BERBAHAN BAKAR E85 (ETANOL 85% & PREMIUM 15%) DENGAN BERBAGAI RASIO KOMPRESI - Majanasastra, R. Bagus Suryasa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2010)
The use of E85 fuel (mixture of 85% ethanol and 15% premium) for gasoline engines requires some changes in the parameter to keep arid improve engine performance. It is caused differences in physical and chemical propertie between Premium, E85 and Ethanol. The purpose this research was to determine the appropriate compression ratiothat can produce high performance at 113.7 cc gasoline engine fueled E85 (Ethanol85% and 15% Premium). Variations do increase the compression ratio of 0.25 ranging from 9.25 to 10.25. The results of this research supports that the best compression ratiofor the motor 113.7 cc 4 stroke gasoline-fueledE85 is 10.25. In the compression ratio isobtained by a maximum engine power 4.5 HP (revolutions 4500 to 5000 rpm) and the average engine power of 3.4 HP. The average specific fuel consumption (BSFC) 0.34Kg /HP Hour. Average CO emissions by 5.8%. Average HC emissions by 240.5 ppm, the average AFR by 0.8